Bilateral Patterns of Repetitive Movements in 6- to 12-Month-Old Infants with Autism Spectrum Disorders - Purpura, Giulia; Costanzo, Valeria; Chericoni, Natasha; Puopolo, Maria; Scattoni, Maria Luisa; Muratori, Filippo; Apicella, Fabio (Frontiers in Psychology, 2017)
Aim: Some patterns of repetitive movements and their frequency have been proved to distinguish infants with Autism Spectrum Disorders (ASD) from infants with Typical Development (TD) and Developmental Delay (DD) from 12 months of life on. The purpose of this study is to investigate if a specific repertoire of repetitive movements is present earlier in life, and if their higher rate and duration could differentiate infants with ASD from infants with DD and TD aged between 6 and 12 months. Method: We conducted a retrospective analysis of video-clips taken from home videos to compare the frequency and the duration of Repetitive Movement Episodes (RMEs) in a sample of 30 children equally distributed among the three groups. Results: Significantly higher total scores in bilateral RMEs with arms, hands, fingers and lower limbs were found to distinguish ASD infants from both DD and TD infants, with a satisfactory diagnostic efficiency. No significant difference was found between the distributions of unilateral RMEs between ASD and DD/TD. Interpretation: Results indicate the presence at this age of an ASD-specific pattern of bilateral repetitive movements. We hypothesize a continuum between this pattern and the lack of variability in finalized and communicative movements and gestures observed in children with ASD during the second year of life.